(untitled) (Journal of the College of Basic Education, 2026)
This study aims to examine emotional confidence among kindergarten teachers. To achieve this goal, the researcher used the descriptive research method. The study population consisted of kindergarten teachers in Wasit Governorate. A sample of 400 teachers was selected using a stratified random sampling method with proportional distribution. To measure emotional confidence, the researcher adopted the Jaber Saddam Scale (2016), based on Lindenfeld’s (2014) theory. The scale consisted of 40 items. The psychometric properties of the scale’s items were verified through discriminatory power and the correlation coefficient between the items and the total score. The validity and reliability of the scale were also confirmed, with the test-retest reliability coefficient reaching 0.840, while the Cronbach’s alpha coefficient reached 0.833. For statistical analysis, the researcher used Pearson’s correlation coefficient, a one-sample t-test, a two-sample independent test, and Cronbach’s alpha equation. The study results revealed that participants demonstrated a high level of self-advocacy.